VASUDHAIVA KUTUMBAKAM DAN TRI HITA KARANA SEBAGAI MEDIA KOMUNIKASI HINDU DALAM MELESTARIKAN BUDAYA - Komang Sarjani Putri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Globalization has shifted modern lifestyles toward technology and material progress, oftensidelining cultural traditions and religious values. This poses challenges for preserving Indonesia’sdiverse cultural heritage. This article examines the Hindu concepts of Vasudhaiva Kutumbakam andTri Hita Karana as intergenerational communication frameworks to sustain culture and strengthensocial harmony. Using a qualitative approach with interviews and literature review, the studyhighlights how Vasudhaiva Kutumbakam—the vision that the world is one family—fosters respectbeyond religious, ethnic, and national boundaries. Meanwhile, Tri Hita Karana emphasizes harmonybetween humans and God, among fellow humans, and with the environment as the basis of well-being. Both concepts serve not only as tools for cultural preservation but also as principles forinclusive communication and solidarity. Their application offers a relevant strategy for maintainingcultural identity and promoting unity in the era of globalization.